PENGARUH WAKTU TINGGAL TERHADAP PERPANDING BOD DAN COD SERTA PEMBENTUKAN GAS METAN (CH4) - Indriyati, Indriyati (Jurnal Teknologi Lingkungan, 2004)
Generally, food wastewater contains high organic matter, therefore the exact wastewater treatment is biological process by using Fixed Bed reactor in anaerobic system. In this observation , showed the comparison between BOD and COD, mass balance and the forming of methane gas (CH4) with variation of hydraulic retention time 11 days, 7 days, 5 days and 3 days. Based on the observation result, the 11 days hydraulic retention time is the most efficient of reactor performance and the best forming of methane gas (CH4) is the 7 days of hydraulic retention.